HUMAN AND THE ATTITUDE OF NATURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper examines the relationship between humans and nature, focusing on the impact of human activities and the responsibility to protect the environment. It emphasizes the importance of developing ecological awareness, preserving natural resources, and safeguarding the environment for future generations. The study concludes that a respectful and responsible attitude towards nature is a key factor in sustainable development and social progress.